2012
DOI: 10.1111/j.1365-2834.2012.01456.x
|View full text |Cite
|
Sign up to set email alerts
|

How magnetic are Finnish hospitals measured by transformational leadership and empirical quality outcomes?

Abstract: Aim  The overall aim of this study was to examine nurses’ and patients’ perceptions of the Magnet model components of transformational leadership and empirical quality outcomes in four Finnish hospitals and to determine if the evidence for transformational leadership and empirical quality outcomes is the same or different in the four hospitals. Background  This report presents baseline measurements for a longitudinal study of the adaptation of the Magnet model in Finnish hospitals. Methods  Web‐based surveys a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
153
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(167 citation statements)
references
References 28 publications
(126 reference statements)
13
153
0
1
Order By: Relevance
“…In term of quality of patient care, the nurse assessed quality of patient care very high quality as expressed by them. This result on the same line with Kvist found that Staff's evaluations of the quality of work in their respective working units had a clear relationship with experiences of job satisfaction [1]. Those who evaluated the quality of work as excellent also rated their job satisfaction to be the highest in all subscales (P<0.0001).…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…In term of quality of patient care, the nurse assessed quality of patient care very high quality as expressed by them. This result on the same line with Kvist found that Staff's evaluations of the quality of work in their respective working units had a clear relationship with experiences of job satisfaction [1]. Those who evaluated the quality of work as excellent also rated their job satisfaction to be the highest in all subscales (P<0.0001).…”
Section: Discussionsupporting
confidence: 79%
“…Added tangible activities are required for effective development to create patient safety culture as supporting of nurse managers and leaders at all levels and nurse staffing evidence Kvist [1]. Asserted by Mahran and Ibrahim emphasized approximately half of studied nurses expressed that patient safety was very good [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, adequate social support and authentic leadership has been found to be an important determinant of positive work outcomes for newly-graduated RNs (Peterson et al 2011, Bjerknes & Bjørk 2012, Laschinger 2012. In Finland, the visibility of nursing managers and administrative leadership styles have been recognised as areas in need of development (Kvist et al 2013).…”
Section: Discussionmentioning
confidence: 98%
“…The themes were mostly drawn from the results of the At Safe Project, e.g. Eneh et al [23] and Kvist et al [30]. They were health promotion, rewarding and feedback, human resource planning and evaluation, patient safety, the management of expertise, change management and well-being at work.…”
Section: Methodsmentioning
confidence: 99%